1980
DOI: 10.1016/s0022-5347(17)56069-3
|View full text |Cite
|
Sign up to set email alerts
|

Primary Grade 1 Transitional Cell Carcinoma of the Renal Pelvis and Ureter

Abstract: During a 22-year period 224 patients were seen for treatment of transitional cell carcinoma of the renal pelvis or ureter. Of these patients 49 (22 per cent) had grade 1 lesions. Followup ranged from 5 to 25 years. The most common symptom was hematuria. In only 54 per cent of the 49 patients was a filling defect noted on excretory urography. Forty-seven patients (96 per cent) had stage I disease. Treatment included total nephroureterectomy, nephrectomy or segmental resection. In 11 patients (23 per cent) evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
71
1
7

Year Published

1985
1985
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(84 citation statements)
references
References 13 publications
5
71
1
7
Order By: Relevance
“…Grade and stage are closely related, and the vast majority of World Health Organization Grade 1 (of 3) urothelial carcinomas are noninvasive, whereas the majority of higher grade tumors show invasion into the lamina propria or muscle layer (7). Previous studies at the Mayo Clinic showed that survival in patients with low-grade urothelial cancers of the upper urinary tract is identical to age-matched controls (20), whereas survival of patients with higher grade tumors correlated with advanced stage and was sig- All data are n. nificantly lower than patients with low-grade tumors and control patients (21,22). In our study, there was no difference in cancer-specific survival between patients with renal pelvic and ureteral cancers (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Grade and stage are closely related, and the vast majority of World Health Organization Grade 1 (of 3) urothelial carcinomas are noninvasive, whereas the majority of higher grade tumors show invasion into the lamina propria or muscle layer (7). Previous studies at the Mayo Clinic showed that survival in patients with low-grade urothelial cancers of the upper urinary tract is identical to age-matched controls (20), whereas survival of patients with higher grade tumors correlated with advanced stage and was sig- All data are n. nificantly lower than patients with low-grade tumors and control patients (21,22). In our study, there was no difference in cancer-specific survival between patients with renal pelvic and ureteral cancers (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The oncological outcomes for patients with high-grade or non-organ-confined disease remain poor, with 5-year cancer-specific survival rates of <60%; while for patients with non-muscle-invasive lesions, the 5-year recurrence-free survival rate is 88.0-91.8% (11). For patients with low-grade carcinomas, conservative strategies, including segmental ureterectomy or endoscopic management, provide cancer-specific survival (CCS) and overall survival (OS) rates equivalent to that achieved using RNU (12,13), with a 5-year cancer-specific survival rate of >93% (14), whereas patients at high-risk (pT3 or N+) may benefit from neoadjuvant chemotherapy (15,16). The ability to accurately predict pathological outcomes prior to initiating therapy may aid in clinical risk stratification and the selection of therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Albeit low-stage and low-grade tumors tend to be associated with good survival aft er either radical or nephron-sparing surgery 6 , high-grade and high-stage tumors can be controlled in a diffi cult manner by nephroureterectomy 7 . Although the tumor presented here was a low-grade one, the outcome was poor, probably due to the tumor seeding at the nephrostomy tract.…”
Section: Discussionmentioning
confidence: 99%